Paradara: Offence in Decency in The Perspective of Hindu Law Occuring in Denpasar City - Alit Putrawan, I Nyoman (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 9 No 2 (2020), 2020)
The purpose of this study to  discuss the  paradara  phenomena that occur in Denpasar and its causal factors as well as sanctions. This  research is an empirical legal research conducted in the city of Denpasar. Primary data obtained through observation and interview techniques. The secondary data obtained through library research. The forms of paradara cases that occur in the city of Denpasar, among others: rape, sexual abuse of children, and adultery. The factors causing the paradara are unwise use of social media, economic factors, family factors and social environment. Sanctions that can be imposed on perpetrators of paradara are criminal as stipulated in Article 284 of the Criminal Code and imposition of customary sanctions. In Hindu law, the prohibition of paradara is regulated in several sacred libraries, including: Manawadharmasastra, such as Manawa Dharmasastra, Sulwasutra, Jyotisastra, and Purana. According to Hindu law, women must be respected and get the highest place.